UK Drugs Unlimited
XVI, 182 p. 2 illus.
Keywords: The appetite for illicit drugs in the UK continues to grow and diversify. Young Britons consume more drugs than their peers anywhere else in Europe. Why and how has this happened and why have all official efforts to stem drug 'abuse' so far failed. Will the new UK drugs strategy fair any better? This unique collection of contemporary studies from the frontline by a leading social research group describes the drugs landscape in an accessible and authoritative way.